Principais fatores que afetam a produtividade nas indústrias de Pato Branco - Secco, Willian (2014)
The present study sought to investigate an appointment raised by the media with some frequency in the past two years: Brazil takes great disadvantage in productivity. Compared with the U.S., the Brazilian worker generates only one-fifth of the wealth generated by American. Accordingly, we sought to understand well what is considered Productivity and the factors affecting it. Subsequent to that, via a questionnaire completed, we investigated how these factors affect level and productivity of industries. The survey sample comprised some industries the city of Pato Branco, Paraná Southwest. The perception of some managers, especially the metallurgical sectors, relative to the level of impact that each of these factors has on the productivity of companies has been verified.